Analisis keunggulan untuk pengembangan peternakan di Kabupaten Halmahera Selatan - ADAM, Syaiful Abdul Radjak ([Yogyakarta] : Universitas Gadjah Mada, 2010)
To provide judgment regarding with animal agriculture development program in The District of South Halmahera, North Maluku Province, a study was conducted using secondary data from Central Bureau of Statistics and Proffincial Office of Agriculture Service. The analysis methods of location quotient (LQ), dynamic location quotient (DLQ), shift-share, growth ratio model, overlay and Klassen typology were performed. The results of the study showed that present leading commodities were goat and village or local chicken. Cattle was found to be inferior in terms of economic growth compared to the provincial average, but can be considered as a future leading commodity. These findings conform to the District Development Program. Swine, duck, broiler and layer were found to have DLQ < 1, meaning that these commodities were not leading commodities. Most of people were Moslem who are not allowed to consumed pork. So far, most farmers are not familiar with broiler and layer. Besides, there have been problems of large capital required, as well as the problems of day-old chicks, feed, vaccines and other inputs supplies.